Alumina-loaded non-noble metal double-site synergistic catalyst, preparation method and application
By using alumina-supported non-precious metal two-site synergistic catalysts in the catalyst, the problems of high cost of existing catalysts and environmental pollution are solved, and an efficient, stable and environmentally friendly propane catalytic dehydrogenation and propylene are achieved.
Patent Information
- Application Number
- CN202411959485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
The existing catalysts for catalytic dehydrogenation of propylene mainly rely on precious metals such as platinum and heavy metals such as chromium, resulting in high costs, serious environmental pollution and difficulty in achieving green development.
Alumina-supported non-precious metal dual-site synergistic catalyst was used to prepare by sol-gel method. Using γ-Al2O3 as a support, non-precious metal nanoparticles and highly dispersed metal oxides were synergistically catalyzed to form a coordinated catalytic activity center.
It achieves the effects of high propane conversion, good propylene selectivity and good reaction stability, while reducing costs and being environmentally friendly.
Smart Images

Figure CN119657109A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and in particular to an alumina-supported non-precious metal dual-site synergistic catalyst, a preparation method and an application thereof. The preparation method is a method for preparing an alumina-supported non-precious metal dual-site synergistic catalyst by a sol-gel method. Background Art
[0002] As a representative of low-carbon olefins, propylene occupies an important position in modern industry, but for a long time it has been mainly produced by naphtha cracking in the petroleum industry. This process has high reaction temperature, high energy consumption, and complex products. Propane is produced by catalytic dehydrogenation of propane, which requires a relatively low reaction temperature, high selectivity for propylene in the reaction product, and a wide range of propane sources. The shale gas revolution has brought a large number of cheap low-carbon alkanes. The dehydrogenation of propane to propylene has the conditions for industrial production, and this technical route has been widely studied.
[0003] In the research and development of catalysts for the catalytic dehydrogenation of propane to propylene, the mainstream catalysts are still the precious metal catalytic systems represented by platinum-based catalysts and the highly toxic heavy metal catalyst systems represented by chromium-based catalysts. Although platinum-based catalysts are optimized through strategies such as alloying dispersion or encapsulation, their cost is still high and the regeneration procedure is complicated. Chromium-based catalysts are highly harmful to the environment and do not meet the requirements of green development in today's era. Therefore, the development of a catalyst with high propane conversion rate, good propylene selectivity, good reaction stability, environmental friendliness, and low cost has become a hot topic in current research.
[0004] γ-Al2O3 is one of the commonly used catalyst carriers. It has weak acidity, low cost, high thermal stability, large specific surface area, and a large number of hydroxyl groups. It is an excellent multiphase catalyst carrier. The current industrialized ethane and propane catalytic dehydrogenation catalyst carrier is γ-Al2O3. We use non-precious metals as active components, γ-Al2O3 as a carrier, and an appropriate amount of alkali metals or alkaline earth metals as additives. We use ammonium carbonate or ammonia water to obtain a catalyst gel precursor, and then age, dry, calcine and reduce the catalyst gel precursor to prepare a catalyst for propane catalytic dehydrogenation with active metal nanoparticles and highly dispersed active metal oxides. The catalyst has achieved good results. The catalyst prepared by this method has not been reported yet. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an alumina-supported non-precious metal dual-site synergistic catalyst, a preparation method and an application. The catalyst is a γ-Al2O3-supported heterogeneous catalyst having a synergistic catalytic function of non-precious metal nanoparticles and highly dispersed metal oxides for efficient catalytic dehydrogenation of propane. The catalyst provided by the present invention is cheap and environmentally friendly, and is used for catalytic dehydrogenation of propane to produce propylene, with high propane conversion rate, good propylene selectivity and good reaction stability.
[0006] The alumina-supported non-precious metal dual-site synergistic catalyst provided by the present invention comprises γ-Al2O3 and a non-precious metal supported on the γ-Al2O3. The γ-Al2O3 has a significant lamellar stacking structure and is prepared in one pot with an active metal and an auxiliary agent during the catalyst preparation process; the non-precious metal comprises an auxiliary agent and an active metal; the auxiliary agent comprises one or more of Na, K, Ca, Li and Mg; the active metal comprises two or more of V, Y, Zr, Mo, W, Mn, Zn, Fe, Co, Ni, Cu and Ga.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] An alumina-supported non-precious metal dual-site synergistic catalyst comprises γ-Al2O3 and a non-precious metal supported on the γ-Al2O3; the non-precious metal comprises an additive and an active metal; the additive comprises one or more of Na, K, Ca, Li and Mg; the active metal comprises two or more of V, Y, Zr, Mo, W, Mn, Zn, Fe, Co, Ni, Cu and Ga; based on the mass of the carrier of the catalyst, the total loading amount of the non-precious metal in the catalyst is 5-50 wt%, and the loading amount of the additive in the catalyst is 0.0%-2.0 wt%. For example, the additive comprises one or more of Na, K, Ca, Li and Mg, and for example, based on the mass of the carrier of the catalyst, the loading amount of the additive in the catalyst is 0.0%, 0.5 wt%, 1.0 wt%, 1.7 wt% or 2.0 wt%. For example, based on the mass of the support of the catalyst, the active metal loading in the catalyst is 5.0 wt%, 13.0 wt%, 21.0 wt%, 28.0 wt%, 36.0 wt%, 42.0 wt% or 50.0 wt%. For example, based on the mass of the support of the catalyst, the total loading of non-noble metals in the catalyst is 5.0 wt%, 13.0 wt%, 21.0 wt%, 28.0 wt%, 36.0 wt%, 42.0 wt% or 50.0 wt%.
[0009] Furthermore, the γ-Al2O3 has a significant lamellar stacking structure and is prepared in one pot with active metals and additives during the catalyst preparation process. Aluminum nitrate is converted into aluminum hydroxide gel by a coagulant, and active metals and additives are either deposited or free in the gel network. In the subsequent aging, drying and calcination processes, the surface hydroxyl groups make the active metal highly dispersed and stable.
[0010] Furthermore, the dual site is: during the catalyst preparation process, two or more non-precious metals are more likely to form highly dispersed metal acid salts than directly interacting with the carrier, and during the reduction process, a portion of the easily reduced active metals form metal nanoparticles with strong H2 activation ability, and another portion of the active metals form partially reduced metal oxides that can remain highly dispersed on the carrier surface. The two form metal nanoparticles and metal oxides through H overflow or reverse overflow to form synergistic catalytic active centers.
[0011] The present invention provides a method for preparing the alumina-supported non-precious metal dual-site synergistic catalyst described in the above technical solution, comprising the following steps:
[0012] (1) Preparation of catalyst gel precursor.
[0013] (2) Aging the catalyst gel precursor under stirring, and then drying, calcining and reducing in sequence to obtain the alumina-supported non-precious metal dual-site synergistic catalyst.
[0014] Specifically, the preparation method of the alumina-supported non-noble metal dual-site synergistic catalyst comprises the following steps:
[0015] Weigh the soluble salt of the active metal and the soluble salt of the auxiliary agent and add water or a mixed solvent of water and ethanol to dissolve them at room temperature to 90°C. After dissolution, add aluminum nitrate nonahydrate and dissolve it completely under stirring to obtain a non-precious metal precursor solution. Weigh ammonium carbonate or ammonia water (25wt%) and add water to form a solution at room temperature as a coagulant for preparing gel. Add the coagulant dropwise to the precursor solution under stirring at room temperature to 90°C to form a gel.
[0016] The catalyst gel precursor is aged under stirring at room temperature to 90° C., and then dried, calcined and reduced in sequence to obtain the alumina-supported non-precious metal dual-site synergistic catalyst.
[0017] Furthermore, the soluble salt of the active metal is two or more of yttrium nitrate, manganese nitrate, zinc nitrate, iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, zirconium nitrate, zirconium oxynitrate, ammonium molybdate tetrahydrate, ammonium tungstate, vanadyl oxalate, vanadyl sulfate and gallium nitrate.
[0018] The soluble salt of the auxiliary agent is one or more of sodium nitrate, potassium nitrate, magnesium nitrate and calcium nitrate. Further, in step (2), the molar concentration of the auxiliary metal ion in the precursor solution is preferably 0-0.10 mol / L, the total molar concentration of the active metal ion is preferably 0.08-1.20 mol / L, and the carrier metal ion: Al 3+ The molar concentration of the ion substance is preferably 1 to 4 mol / L. For example, the molar concentration of the auxiliary metal ion substance in the precursor solution is 0.00 mol / L, 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.08 mol / L or 0.10 mol / L; the molar concentration of the active metal ion substance is 0.08 mol / L, 0.24 mol / L, 0.32 mol / L, 0.40 mol / L, 0.48 mol / L, 0.56 mol / L, 0.64 mol / L, 0.72 mol / L, 0.80 mol / L, 0.88 mol / L, 0.96 mol / L, 1.04 mol / L, 1.12 mol / L or 1.20 mol / L; Al 3+ The molar concentration of the ion substance is 1.0 mol / L, 2.0 mol / L, 3.0 mol / L or 4.0 mol / L.
[0019] Preferably, in step (2), the aging is to age the catalyst gel precursor under stirring at room temperature to 90° C. for 0 to 5 hours.
[0020] Preferably, in step (2), the drying temperature is 80-120° C. and the drying time is 8-12 h.
[0021] Preferably, in step (2), the calcination temperature is 300-900°C, the time is 0-3 h, and the calcination is carried out in an air atmosphere. For example, in step (2), the calcination temperature is 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, and the time is 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.
[0022] Preferably, in step (2), the reduction is hydrogen or CO reduction, and the hydrogen or CO reduction is carried out in a mixture of H2 or CO and Ar, wherein the volume concentration of H2 or CO in the mixture is 5-100%; the reduction temperature is 400-600°C, and the time is 0.1-2 h. For example, the reduction temperature is 400°C, 450°C, 500°C, 550°C or 600°C, and the time is 0.1 h, 0.2 h, 0.5 h, 1 h, 1.5 h or 2 h.
[0023] The present invention provides application of the catalyst described in the above technical solution or the catalyst prepared by the preparation method described in the above technical solution in the reaction of catalytic dehydrogenation of propane to produce propylene.
[0024] Preferably, the feed gas for the propane catalytic dehydrogenation to propylene reaction comprises C3H8 and Ar, the volume ratio of C3H8 to Ar is (2-20):(80-0), and the propane feed space velocity of the feed gas is 240-2400 mL·g -1 ·h -1 .
[0025] Preferably, the temperature of the propane catalytic dehydrogenation to propylene reaction is 450-650° C. For example, the temperature of the propane catalytic dehydrogenation to propylene reaction is 450° C., 500° C., 550° C., 600° C. or 650° C.
[0026] The present invention has the following beneficial effects:
[0027] The present invention provides an alumina-supported non-precious metal dual-site synergistic catalyst, comprising γ-Al2O3 and a non-precious metal supported on the γ-Al2O3. The non-precious metal comprises an additive and an active metal; the additive comprises one or more of Na, K, Ca, Li and Mg; the active metal comprises two or more of V, Y, Zr, Mo, W, Mn, Zn, Fe, Co, Ni, Cu or Ga. The present invention uses γ-Al2O3 as a carrier, and γ-Al2O3 has a significant lamellar stacking structure; the present invention uses non-precious metals as active metals; the present invention uses a sol-gel method as a preparation method; the active metal ions are either deposited or free in the aluminum hydroxide gel network with the assistance of a coagulant, and form metal acid salts during the aging, drying and roasting processes, and are tightly combined with the carrier and highly dispersed. In the subsequent reduction process, part of the metal in the metal salt is completely reduced to form a metal nanoparticle active center with the ability to activate H2, and part of the metal is partially reduced to form a highly dispersed metal oxide active center. The two active centers form a synergistic catalytic active center through H overflow or reverse overflow, thereby promoting the activation of propane and the desorption of propylene, and more significantly promoting the generation and desorption of H2, greatly improving the catalytic performance of the catalyst. The aluminum oxide-supported non-precious metal dual-site synergistic catalyst provided by the present invention is cheap and environmentally friendly, and is used for the catalytic dehydrogenation of propane to produce propylene, with high propane conversion rate, good propylene selectivity, and good reaction stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The XRD diagrams of the catalysts obtained in Example 2 and Comparative Examples 1-2 are shown;
[0029] Figure 2 H2-TPR curves of the catalysts obtained in Example 2 and Comparative Examples 1-2;
[0030] Figure 3 TEM images of the catalyst obtained in Example 2 at different scales;
[0031] Figure 4 This is the reuse performance curve of the catalyst obtained in Example 2. DETAILED DESCRIPTION
[0032] The present invention provides an alumina-supported non-precious metal dual-site synergistic catalyst, comprising γ-Al2O3 and a non-precious metal supported on the γ-Al2O3, wherein the non-precious metal comprises an additive and an active metal; the additive comprises one or more of Na, K, Ca, Li and Mg; the active metal comprises two or more of V, Y, Zr, Mo, W, Mn, Zn, Fe, Co, Ni, Cu and Ga.
[0033] In the present invention, the γ-Al2O3 as a carrier has the advantages of low cost, high thermal stability, large specific surface area, and strong interaction with active components. γ-Al2O3 is prepared in one pot with active metals and additives through a sol-gel method, and has a significant lamellar stacking structure. The present invention uses non-precious metals as active components. The active metals preferentially form metal acid salts that are highly dispersed on the surface of the carrier during the preparation process, and form metal nanoparticles with strong H2 activation performance and partially reduced highly dispersed metal oxides during the reduction process. The two constitute a synergistic catalytic active center and form a strong interaction with the carrier.
[0034] In the present invention, the total loading amount of non-precious metals in the catalyst is preferably 5-50 wt% based on the carrier mass. In the present invention, the particle size of the active metal nanoparticles is 0-5 nm, the partially reduced metal oxides are highly dispersed, and no particle structure composed of them is observed.
[0035] The present invention provides a method for preparing the alumina-supported non-precious metal dual-site synergistic catalyst described in the above technical solution, comprising the following steps:
[0036] Weigh the active metal and the additive and add water or a mixed solvent of water and ethanol to dissolve them at room temperature to 90°C. After dissolution, add aluminum nitrate nonahydrate and dissolve it completely under stirring to obtain a non-precious metal precursor solution. Weigh ammonium carbonate or ammonia water (25wt%) and add water to form a solution of concentration at room temperature as a coagulant for preparing gel. Add the coagulant dropwise to the precursor solution under stirring at room temperature to 90°C to form a gel.
[0037] The catalyst gel precursor is aged under stirring at room temperature to 90° C., and then dried, calcined and reduced in sequence to obtain the alumina-supported non-precious metal dual-site synergistic catalyst.
[0038] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0039] The present invention dissolves the soluble salt of the non-precious metal with water or a mixed solvent of water and ethanol to obtain a precursor solution. In the present invention, the soluble salt of the non-precious metal is preferably a nitrate, for example, sodium nitrate, potassium nitrate, calcium nitrate, magnesium nitrate, yttrium nitrate, manganese nitrate, zinc nitrate, iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, zirconium nitrate, zirconium oxynitrate or gallium nitrate, and the soluble salt of the non-precious metal can also be a vanadium salt, a molybdenum salt, a tungsten salt or a lithium salt, the lithium salt is preferably lithium chloride, the vanadium salt is preferably vanadyl oxalate, vanadyl sulfate, the molybdenum salt is preferably ammonium molybdate tetrahydrate, the tungsten salt is preferably ammonium tungstate, and the aluminum salt as a precursor of the carrier is preferably aluminum nitrate.
[0040] In the present invention, the molar concentration of the auxiliary metal ions in the precursor solution is preferably 0-0.1 mol / L, the total molar concentration of the active metal ions is preferably 0.08-1.2 mol / L, and the carrier metal ions are preferably Al 3+ The molar concentration of the ions is preferably 1 to 4 mol / L.
[0041] In the present invention, the γ-Al2O3 is prepared in one pot with active metals and additives by a sol-gel method, and has a significant lamellar stacking structure. The present invention uses non-precious metals as active components. The active metals preferentially form metal acid salts that are highly dispersed on the surface of the carrier during the preparation process, and form metal nanoparticles with strong H2 activation performance and partially reduced highly dispersed metal oxides during the reduction process. The two constitute a synergistic catalytic active center and form a strong interaction with the carrier.
[0042] In the present invention, the dissolution temperature of the catalyst precursor solution is preferably 0-90°C. In the embodiment of the present invention, the dissolution is preferably performed at 70°C.
[0043] In the present invention, the aging temperature of the catalyst precursor gel is preferably 0-90°C. In the embodiment of the present invention, the aging is preferably carried out at 70°C.
[0044] In the present invention, the drying temperature is preferably 80-120 ° C, and the time is preferably 8-12 h. In an embodiment of the present invention, the drying is preferably carried out in an oven, and the drying temperature is preferably carried out at 100 ° C. In the present invention, the calcination temperature is preferably 300-900 ° C, more preferably 450 ° C, 500 ° C, 550 ° C or 600 ° C, 650 ° C, 700 ° C, the time is preferably 3 h, and the calcination is preferably carried out in an air atmosphere. In an embodiment of the present invention, the calcination is preferably carried out in a muffle furnace. During the calcination process, the active metal salt further interacts and anchors to the surface of γ-Al2O3. The dispersion and structure of the active metal acid salt and the bonding strength with the carrier can be adjusted by adjusting the calcination temperature, so that the catalytic performance can be regulated.
[0045] In the present invention, the reduction is preferably hydrogen or CO reduction, and the hydrogen or CO reduction is preferably carried out in a mixed gas of H2 or CO and Ar, and the volume concentration of H2 or CO in the mixed gas is preferably 5-100%, more preferably 10-30%; the temperature of the reduction is preferably 500°C, and the time is preferably 0.1-2 h. In the present invention, the sample obtained after calcination is preferably loaded into a fixed bed reaction tube, the mixed gas is introduced, and the reduction is carried out at 500°C.
[0046] The preparation method provided by the invention is simple and can be easily scaled up for production.
[0047] The present invention provides the use of the alumina-supported non-precious metal dual-site synergistic catalyst described in the above technical solution or the alumina-supported non-precious metal dual-site synergistic catalyst prepared by the preparation method described in the above technical solution in the catalytic dehydrogenation of propane to propylene reaction.
[0048] In the present invention, the raw gas for the reaction preferably includes C3H8 and Ar, and the volume ratio of C3H8 to Ar is (2-20):(80-0), more preferably (3.0-30):(18-0). In the present invention, the propane feed space velocity (WHSV) of the raw gas is preferably 240-2400 mL·g -1 ·h -1 , more preferably 360~1200 mL·g -1 ·h -1 In the present invention, the reaction temperature is preferably 450-650°C, more preferably 500-580°C.
[0049] The alumina-supported non-precious metal dual-site synergistic catalyst provided by the present invention is used for the catalytic dehydrogenation of propane to produce propylene, and can show good catalytic activity and selectivity, and can obtain propylene products with a high yield. The catalyst provided by the present invention has the advantages of good catalytic performance, high stability, good selectivity, low cost, strong practicality, and reusability, and provides a new industrializable non-precious metal environmentally friendly catalytic system for the catalytic dehydrogenation of propane to produce propylene.
[0050] To further illustrate the present invention, the alumina-supported non-precious metal dual-site synergistic catalyst provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0051] Example 1
[0052] Weigh 495.9 mg of cobalt nitrate hexahydrate, 524.8 mg of vanadyl oxalate, and 202.2 mg of calcium nitrate tetrahydrate and dissolve them in 20 mL of water, then add 14700.0 mg of aluminum nitrate nonahydrate and stir and dissolve them in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g of ammonium carbonate and dissolve it in 35 ml of water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a 500 °C muffle furnace and calcined for 3 h under air conditions; after cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration, based on the total volume of the H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 °C for reduction for 2 h to obtain Co: V: Ca=1: 2: 0.5 (molar ratio) and CoV2Ca with a Co loading of 5 wt% (based on the mass of the carrier of the catalyst) 0.5 O x / γ-Al2O3 catalyst, denoted as C-1.
[0053] Example 2
[0054] Weigh 495.5 mg of nickel nitrate hexahydrate and 555.5 mg of vanadyl sulfate and dissolve them in 20 mL of water. Then add 14700.0 mg of aluminum nitrate nonahydrate and stir and dissolve them in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g of ammonium carbonate and dissolve it in 35 ml of water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a muffle furnace at 500 °C and calcined for 3 h under air conditions; after cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration based on the total volume of the H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 °C for reduction for 2 h to obtain NiV2O with Ni:V =1:2 (molar ratio) and Ni loading of 5wt% (based on the mass of the carrier of the catalyst) x / γ-Al2O3 catalyst, denoted as C-2.
[0055] Example 3
[0056] Weigh 495.5 mg nickel nitrate hexahydrate, 555.5 mg vanadyl sulfate, and 202.2 mg calcium nitrate tetrahydrate and dissolve them in 20 mL water, then add 14700.0 mg aluminum nitrate nonahydrate and stir and dissolve in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g ammonium carbonate and dissolve it in 35 ml water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a 500 °C muffle furnace and calcined for 3 h under air conditions; after cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration based on the total volume of the H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 °C for reduction for 2 h to obtain NiV2Ca with Ni:V:Ca=1:2:0.5 (molar ratio) and Ni loading of 5wt% (based on the mass of the carrier of the catalyst) 0.5 O x / γ-Al2O3 catalyst, denoted as C-3.
[0057] Example 4
[0058] Weigh 495.5 mg nickel nitrate hexahydrate, 601.7 mg ammonium molybdate tetrahydrate, and 202.2 mg calcium nitrate tetrahydrate and dissolve them in 20 mL water, then add 14700.0 mg aluminum nitrate nonahydrate and stir and dissolve them in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g ammonium carbonate and dissolve it in 35 ml water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a 500 °C muffle furnace and calcined for 3 h under air conditions; after cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration based on the total volume of the H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 °C for reduction for 2 h to obtain NiMo2Ca with Ni:Mo:Ca=1:2:0.5 (molar ratio) and Ni loading of 5wt% (based on the mass of the carrier of the catalyst) 0.5 O x / γ-Al2O3 catalyst, denoted as C-3, denoted as C-4.
[0059] Comparative Example 1
[0060] Weigh 495.5 mg nickel nitrate hexahydrate and 202.2 mg calcium nitrate tetrahydrate and dissolve them in 20 mL water, then add 14700.0 mg aluminum nitrate nonahydrate and stir and dissolve them in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g ammonium carbonate and dissolve it in 35 ml water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a 500 °C muffle furnace and calcined for 3 h under air conditions; after cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration based on the total volume of the H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 °C for reduction for 2 h to obtain NiCa with Ni:Ca=1:0.5 (molar ratio) and Ni loading of 5wt% (based on the mass of the carrier of the catalyst) 0.5 O x / γ-Al2O3 catalyst, denoted as, denoted as C-5.
[0061] Comparative Example 2
[0062] Weigh 555.5 mg of vanadyl sulfate and 202.2 mg of calcium nitrate tetrahydrate and dissolve them in 20 mL of water, then add 14700.0 mg of aluminum nitrate nonahydrate and stir and dissolve them in an oil bath at 70°C to obtain a precursor metal solution. Weigh 0.5 g of ammonium carbonate and dissolve it in 35 ml of water to obtain an ammonium carbonate solution. After both are completely dissolved, add the ammonium carbonate solution dropwise to the precursor metal solution in this state to obtain a catalyst precursor gel. Keep the temperature and stirring to age the precursor gel for 3 hours, move it into an oven, and dry it at 100°C for 10 hours. The dried sample was placed in a porcelain boat, and then placed in a 500 ℃ muffle furnace and calcined in air for 3 h. After cooling to room temperature, 0.5 g of the sample was taken and loaded into a fixed bed reaction tube, and 10% (H2 volume concentration based on the total volume of H2 / Ar mixed gas) H2 / Ar mixed gas was passed through at 500 ℃ for reduction for 2 h to obtain NiV2Ca with V:Ca = 2:0.5 (molar ratio) and Ni loading of 5wt%. 0.5 O x / γ-Al2O3 has the same V loading amount of V2Ca 0.5 O x / γ-Al2O3 catalyst, denoted as C-6.
[0063] Structure and performance characterization
[0064] The catalyst samples obtained in Example 2 and Comparative Examples 1-2 were characterized by XRD. The results are as follows: Figure 1As shown in the figure, the catalyst C-2 (NiV2O x / γ-Al2O3) and Comparative Example C-6 (V2Ca 0.5 O x / γ-Al2O3) only shows the characteristic peak of γ-Al2O3 in the XRD spectrum of the catalyst, and no characteristic peaks of active metals and their oxides are found, indicating that the active metals of the catalyst samples obtained in both comparative examples and examples are highly dispersed on γ-Al2O3. 0.5 O x / γ-Al2O3) shows not only the characteristic peaks of γ-Al2O3 but also some Ni2Al 18 O 29 This indicates that in the absence of V, Ni can interact strongly with γ-Al2O3 to generate Ni species in the nickel aluminate series that are difficult to reduce. When Ni and V coexist, the two are more likely to interact with each other, thereby hindering the generation of aluminate series species.
[0065] The catalyst samples obtained in Example 2 and Comparative Examples 1-2 were characterized by H2-TPR. Figure 2 As shown, C-2 (NiV2O x The reduction temperature of the catalyst ( / γ-Al2O3) is significantly lower than that of the single metal catalyst, indicating that the active metals of the catalyst are more likely to interact with each other than the carrier, which also verifies the conclusion drawn by XRD. It is also for this reason that the reduced active metal nanoparticles and partially reduced active metal oxides can be closely adjacent to each other, achieving a better synergistic catalytic effect.
[0066] The catalyst sample obtained in Example 2 was characterized by TEM. Figure 3 As shown in both macroscopic and microscopic images, active metal Ni nanoparticles and VO x There was no significant aggregation of species. Figure 3 a and b show the macroscopic structure of the catalyst, and the carrier γ-Al2O3 in the catalyst presents a lamellar stacking structure; Figure 3 c, d show the lattice fringes of the active metal Ni nanoparticles of the catalyst, with a particle size of < 5 nm, while VO x Highly dispersed, its crystal features cannot be observed.
[0067] The catalyst obtained in Example 2 was tested for its catalytic propane dehydrogenation performance and reusability under the conditions of Application Example 2. The results are shown in Figure 4 .Depend on Figure 4It can be seen that the catalyst reaches a higher activity after 2 hours of reaction, and the catalytic performance decreases slightly after 12 hours of reaction. This indicates that the catalyst prepared by the present invention has good catalytic stability. In subsequent repeated use, it is found that the catalytic activity of the regenerated catalyst is slightly improved compared with the reaction performance of the new catalyst, indicating that although carbon deposition and deactivation occur during the reaction, the distribution of active centers is gradually optimized.
[0068] Application Example 1
[0069] The catalysts prepared in Examples 1-4 and Comparative Examples 1-2 were used in the catalytic dehydrogenation reaction of propane to illustrate the catalytic performance of different catalysts in the catalytic reaction of propane to propylene.
[0070] The catalyst catalytic argon-diluted propane dehydrogenation performance test was carried out under constant temperature and atmospheric pressure of 500 °C. A mixed reaction gas was introduced into 0.5 g of the catalyst obtained by in-situ reduction in the fixed bed reaction tube, wherein C3H8: 3.6 mL / min, Ar: 18 mL / min. The outlet of the fixed bed reaction tube was connected to an Agilent gas chromatograph for product component analysis. The product composition was analyzed by the standard curve method to obtain the content of each component in the product and calculate the propane conversion rate and propylene selectivity. The data of different catalysts reacting for 2 hours are shown in Table 1.
[0071] Table 1 Results of the catalysts prepared in Examples 1 to 13 and Comparative Examples 1 to 12 in the catalytic dehydrogenation of propane to propylene
[0072] As can be seen from Table 1, the catalyst prepared by the present invention has good catalytic activity and propylene selectivity for the reaction of catalytic dehydrogenation of propane to propylene. 0.5 O x / γ-Al2O3) catalyst and C-5 (NiCa 0.5 O x / γ-Al2O3) and C-6 (V2Ca 0.5 O x The performance comparison of the dual-site synergistic catalysis and the γ-Al2O3 shows that the catalytic performance is significantly improved. It provides a practical example for improving catalyst performance and shows the potential of non-precious metal catalysts to replace precious metal catalysts.
[0073] Application Example 2
[0074] Catalyst C-2 (NiV2O x / γ-Al2O3) as an example to illustrate the performance of this series of catalysts in the catalytic dehydrogenation reaction of propane.
[0075] 0.5 g C-2(NiV2O) was obtained by in-situ reduction in a fixed bed reactor at 500 °C under normal pressure for 2 h by introducing 10% (H2 volume concentration based on the total volume of H2 / Ar mixture) H2 / Ar mixture (20 mL / min). x / γ-Al2O3) catalyst, then switched to mixed reaction gas: C3H8: 3.6 mL / min, Ar: 18 mL / min, and maintained at atmospheric pressure and 500 ℃ constant temperature for reaction. The outlet of the fixed bed reaction tube was connected to Agilent gas chromatograph for product component analysis. The product composition was analyzed by standard curve method to obtain the content of each component in the product and calculate the propane conversion rate and propylene selectivity. After 12 hours of reaction, it was cooled to room temperature, taken out and calcined at 500 ℃ in air atmosphere in a muffle furnace for 2 hours. After calcination, it was loaded into the fixed bed reaction tube and reduced again to complete catalyst regeneration. The reaction data of the catalyst reused 3 times is shown in Figure 4 shown.
[0076] from Figure 4 It can be seen that the catalyst prepared by the present invention has good stability and reusability, and the catalytic activity after repeated use for three times is not only not reduced compared with the initial use, but also shows a trend of gradual increase. It should be that although carbon deposition and deactivation will occur during the reaction, the distribution of active centers is gradually optimized.
[0077] It can be seen from the above embodiments and application examples that the alumina-supported non-precious metal dual-site synergistic catalyst prepared by the present invention has a good catalytic effect on the reaction of catalytic dehydrogenation of propane to propylene.
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. An alumina-supported non-noble metal dual-site synergistic catalyst, characterized in that: The catalyst comprises a carrier of γ-Al2O3 and a non-precious metal loaded on the γ-Al2O3; the non-precious metal comprises an additive and an active metal; the additive comprises one or more of Na, K, Ca, Li and Mg; the active metal comprises two or more of V, Y, Zr, Mo, W, Mn, Zn, Fe, Co, Ni, Cu and Ga. Based on the mass of the carrier of the catalyst, the total loading amount of the non-precious metal in the catalyst is 5-50wt%, and the loading amount of the additive in the catalyst is 0.0%-2.0wt%.
2. The alumina-supported non-noble metal dual-site synergistic catalyst according to claim 1, characterized in that: The γ-Al2O3 is prepared in one pot with active metals and additives through a sol-gel method and has a lamellar stacking structure.
3. The alumina-supported non-noble metal dual-site synergistic catalyst according to claim 1, characterized in that: The dual site is: during the catalyst preparation process, two or more active metals are more likely to form highly dispersed metal acid salts than to form strong interactions with the carrier, and during the reduction process, a part of the easily reduced active metals form metal nanoparticles with the ability to activate H2, and another part of the active metals form partially reduced metal oxides that can remain dispersed on the carrier surface; the two form metal nanoparticles and metal oxides through overflow or reverse overflow of H to form synergistic catalytic active centers.
4. The method for preparing the alumina-supported non-noble metal dual-site synergistic catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing catalyst precursor gel; (2) aging the catalyst precursor gel under stirring; and then drying, calcining and reducing in sequence to obtain the alumina-supported non-precious metal dual-site synergistic catalyst.
5. The preparation method according to claim 4, characterized in that: Step (1) comprises: weighing a soluble salt of an active metal and a soluble salt of an auxiliary agent, adding water or a mixed solvent of water and ethanol to dissolve them, the dissolution temperature being room temperature to 90° C., adding aluminum nitrate nonahydrate after dissolution, and dissolving it completely under stirring to obtain a non-precious metal precursor solution; weighing ammonium carbonate or ammonia water, adding water to form a solution at room temperature as a coagulant for preparing a gel.
6. The preparation method according to claim 5, characterized in that: In step (1), the molar concentration of the auxiliary metal ions in the precursor solution is preferably 0-0.1 mol / L, the total molar concentration of the active metal ions is preferably 0.08-1.2 mol / L, and the carrier metal ions are preferably Al 3+ The molar concentration of the ions is preferably 1 to 4 mol / L.
7. The preparation method according to claim 5, characterized in that: In step (1), the coagulant is ammonium carbonate or an aqueous ammonia solution, and its molar concentration is 1-4 mol / L.
8. The preparation method according to claim 4, characterized in that: In step (1), the coagulant is added dropwise to the precursor solution at room temperature to 90° C. under stirring, and the adding time is 5 to 30 minutes.
9. The preparation method according to claim 4, characterized in that: In step (2), the aging temperature is 50-120° C., the time is 1-5 h, and stirring is maintained during the aging period.
10. The preparation method according to claim 4, characterized in that: In step (2), the drying temperature is 80-120°C and the drying time is 8-12 hours.
11. The preparation method according to claim 4, characterized in that: In step (2), the calcination temperature is 300-900°C, the time is 0-3 h, and the calcination is carried out in an air atmosphere.
12. The preparation method according to claim 4, characterized in that: In step (2), the reduction is hydrogen or CO reduction, and the hydrogen or CO reduction is carried out in a H2 / Ar mixed gas or a CO / Ar mixed gas, the volume concentration of H2 in the H2 / Ar mixed gas is 5~100%; the volume concentration of CO in the CO / Ar mixed gas is 5~100%; the temperature of the reduction is 400~600°C, and the time is 0.1~2 h.
13. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 12 in the reaction of catalytic dehydrogenation of propane to produce propylene.
14. The use according to claim 13, characterized in that The feed gas for the propane catalytic dehydrogenation reaction to produce propylene includes C3H8 and Ar, wherein the volume ratio of C3H8 to Ar is (2-20):(80-0), and the propane feed space velocity of the feed gas is 240-2400 mL·g -1 ·h -1 .
15. The use according to claim 13, characterized in that: The reaction temperature is 450-650°C.